2010
DOI: 10.1007/s11255-010-9739-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of video-urodynamic studies before renal transplantation in chronic renal failure patients

Abstract: Video-urodynamic studies before renal transplantation provide earlier diagnosis of lower tract abnormalities, which are likely to cause graft dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…The incidence of bladder dysfunction was previously reported to be high in patients with renal failure . A hypocompliant bladder (decrease in bladder capacity with increase in intravesical pressure) is the main cystometric abnormality in patients who undergo long‐term dialysis . The results of the present study were comparable with those of the previous study by Turunc et al ., who showed that 68% of patients with pretransplant dialysis duration of >5 years had a pretransplant hypocompliant bladder <10 mL/cmH 2 O .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The incidence of bladder dysfunction was previously reported to be high in patients with renal failure . A hypocompliant bladder (decrease in bladder capacity with increase in intravesical pressure) is the main cystometric abnormality in patients who undergo long‐term dialysis . The results of the present study were comparable with those of the previous study by Turunc et al ., who showed that 68% of patients with pretransplant dialysis duration of >5 years had a pretransplant hypocompliant bladder <10 mL/cmH 2 O .…”
Section: Discussionsupporting
confidence: 90%
“…The present study showed that pretransplant bladder compliance also correlated logarithmically with dialysis duration. The incidence of bladder dysfunction was previously reported to be high in patients with renal failure . A hypocompliant bladder (decrease in bladder capacity with increase in intravesical pressure) is the main cystometric abnormality in patients who undergo long‐term dialysis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations